2019
DOI: 10.1080/15592294.2019.1585176
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage-specific genome-wide DNA methylation analysis of patients with paediatric-onset systemic lupus erythematosus

Abstract: 2019) Cell lineage-specific genome-wide DNA methylation analysis of patients with paediatric-onset systemic lupus erythematosus, Epigenetics, 14:4, 341-351, ABSTRACTPatients with paediatric-onset systemic lupus erythematosus (SLE) often present with more severe clinical courses than adult-onset patients. Although genome-wide DNA methylation (DNAm) profiling has been performed in adult-onset SLE patients, parallel data on paediatric-onset SLE are not available. Therefore, we undertook a genome-wide DNAm study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(83 reference statements)
0
14
0
1
Order By: Relevance
“…Recent studies have identified that DNA hypomethylation might contribute to the immune response and over-reactivity in SLE CD4 + T cells (Zhang et al, 2013;Zhao et al, 2014;Yeung et al, 2019). In addition, biochemical modifications to mRNA, especially m 6 A and m 5 C, have also been shown to be of considerable importance with regard to the biological functions of developing disease (Li et al, 2018;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified that DNA hypomethylation might contribute to the immune response and over-reactivity in SLE CD4 + T cells (Zhang et al, 2013;Zhao et al, 2014;Yeung et al, 2019). In addition, biochemical modifications to mRNA, especially m 6 A and m 5 C, have also been shown to be of considerable importance with regard to the biological functions of developing disease (Li et al, 2018;.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the normal balance of activity in CD4 + T cells is associated with the development of SLE (Yin et al, 2015). In addition, epigenetics-based genetic predispositions and their interaction in T cells are thought to contribute to SLE pathogenesis and development (Lei et al, 2009;Yeung et al, 2019); these epigenetic modulators include DNA methylation, DNA 5-hmC, and altered long non-coding RNA expression (Coit et al, 2015;Zhao et al, 2016;Zhang et al, 2018;Guo et al, 2019;Ye et al, 2019). For example, the transcription factor RFX1 affects the epigenetic status of CD4 + T cells, which result in autoimmune responses in SLE (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by others, demonstrating reduced DNA methylation, and increased mRNA expression of type I IFN associated genes in B cells, T cells, monocytes and granulocytes (16). Reduced CpG DNA methylation of type I IFN associated genes is (expectedly) also present in juvenile-onset SLE (123) and contributes to increased type I IFN-induced gene expression patterns (116). Neutrophils, which exhibit even higher IFN-induced gene signatures as compared to other leukocytes (117), have 68% of their CpG sites hypomethylated and 32% hypermethylated (124).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Se ha descrito en varios estudios, en pacientes con LES, la alteración en la porción larga del cromosoma 1, de manera específica la región 1q23-24. No se conoce por completo el mecanismo por el cual los genes de la región del complejo mayor de histocompatibilidad (HLA) podrían determinar la susceptibilidad al LES 1,5,6 . 2.…”
Section: Factores Predisponentes Y Desencadenantes Del Leunclassified